Grain Boundary Sliding in Aluminum Nano‐Bi‐Crystals Deformed at Room Temperature. Issue 1 (19th July 2013) - Aitken, Zachary H.; Jang, Dongchan; Weinberger, Christopher R.; Greer, Julia R.
Abstract Room‐temperature uniaxial compressions of 900‐nm‐diameter aluminum bi‐crystals, each containing a high‐angle grain boundary with a plane normal inclined at 24° to the loading direction, revealed frictional sliding along the boundary plane to be the dominant deformation mechanism. The top crystallite sheared off as a single unit in the course of compression instead of crystallographic slip and extensive dislocation activity, as would be expected. Compressive stress strain data of deforming nano bicrystals was continuous, in contrast to single crystalline nano structures that show a stochastic stress strain signature, and displayed a peak in stress at the elastic limit of ∼176 MPa followed by gradual softening and a plateau centered around ∼125 MPa. An energetics‐based physical model, which may explain observed room‐temperature grain boundary sliding, in presented, and observations are discussed within the framework of crystalline nano‐plasticity and defect microstructure evolution.